MANAGING PALM OIL PLANTATIONS (Elaeis guineensis Jacq.) DURING THE NON-YIELDING PHASE BASED ON THE ANDROID GPS PRECISION INSTRUMENT - Wahyudi, Dedi; Irfan Kamil Siregar; Diki Agustiawan (Agro Estate, 2024)
Problems in managing palm oil plantations often arise when the plantation changes ownership or is sold in less than optimal conditions. New owners often do not understand the corrective steps needed to increase plantation productivity. This study aims to apply Android Global Positioning System (GPS)-based technology to manage palm oil plantations in the non-yielding phase. The research method used in this study is quantitative with a descriptive approach to obtain numerical data, namely the plantation area, ideal plant population, replacement seedling requirements, and total management costs for six months. The study results obtained a measured oil palm plantation area of ​​0.5 ha, the ideal plant population is 71 plants, and the need for replacement palm oil seedlings is 35. The implications of this study provide practical guidance for new oil palm plantation owners to understand the corrective steps needed to start management based on the right budget. The total cost of managing palm oil plantations for six months is Rp. 4,845,500